KKN Tematik Penerapan Teknologi Dalam Rangka Mendukung Pemulihan Ekonomi di Desa Wanajaya - Julianto, Indri Tri; Nurfauziah, Hanifah; Nawawi, Irfan Ahmad; Sanusi, Aini Fauziah Putu; Nurdiansyah, Farhan; Hidayat, Rangga; Ardana, Alwan; Hidayat, Ramdan Rahmat; Pardiansyah, Irgi; Sadikin, M. Fitroh; Dikdik, Dikdik; Nursalapiah, Sopa; Sermana, Elsa Maharani; Aditriyana, Muhammad Rizky; Abdulrohman, Muhammad Haviz; Pratama, Rizky Muhammad; Dinata, Messy Suryani Jaya; Fajar, Sigit Sihab; Octaviansyah, Rizqi Moch; Mulyani, Neng Cici (Institut Teknologi Garut, 2023)
Wanajaya Village is one of the villages in the Wanaraja sub-district, Garut Regency, West Java Province. Administratively, the area of ”‹”‹Wanajaya Village has a sizeable area, directly adjacent to Sukamulya Village and Citangtu Village, Pangatikan Subdistrict, to the south, Sindangratu Village and Wanamekar Village to the south, Sindangratu Village to the east, and Citangtu Village to the east. to the west it is directly adjacent to Wanasari Village, and Wanaraja Village, Wanaraja District. Based on the results of the survey that we have carried out, then with the results obtained from the survey we develop work programs that we will carry out for one month. The work program consists of work programs from various study programs as well as excellent work programs that are worked on directly by all members. In addition to work programs from various study programs and also the superior work programs that we plan, there are several other work programs that we also plan, namely teaching the Koran at mosques, holding August 17 activities, conducting clean Friday activities, conducting computer introduction activities and digitalization to elementary school children, besides that there are several work programs that we did not plan beforehand but there were requests from local residents such as carrying out garbage collection activities, making school profile videos, making the Wanajaya 1 SD school logo, making the Karangtaruna logo, and so on.